2004
DOI: 10.1111/j.1365-2133.2004.06244.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of epidermodysplasia verruciformis-associated human papillomavirus DNA in nongenital seborrhoeic keratosis

Abstract: This study provides some evidence that EV-associated HPVs might play a part in the pathogenesis of nongenital SK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 31 publications
2
52
2
2
Order By: Relevance
“…In addition, other investigators using similar methods have found comparable results: HPV DNA has been detected in 4% to 35% of normal-appearing skin samples. [53][54][55][56][57][58] Coinfection with EV and GM HPV genotypes was found in both EN types (two HPV DNA [EV and GM] and 3 HPV DNA [two EV and one GM]). For NS, 59% harbored EV HPV DNA, and 50% had GM HPV DNA.…”
Section: Hpv Dna Is Frequently Detected In Nsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other investigators using similar methods have found comparable results: HPV DNA has been detected in 4% to 35% of normal-appearing skin samples. [53][54][55][56][57][58] Coinfection with EV and GM HPV genotypes was found in both EN types (two HPV DNA [EV and GM] and 3 HPV DNA [two EV and one GM]). For NS, 59% harbored EV HPV DNA, and 50% had GM HPV DNA.…”
Section: Hpv Dna Is Frequently Detected In Nsmentioning
confidence: 99%
“…This cocktail probe detects the following 12 genotypes: 16,18,31,33,35,39,45,51,52,56,58, and 66. The xenograft control slide, HPV 3 in one system control slides (Ventana Medical Systems Inc), was run for positive and negative controls.…”
Section: Sequencingmentioning
confidence: 99%
“…7 These HPV types are detectable in skin carcinomas, as well as in control specimens of healthy skin from the general population. [8][9][10][11][12] There are more than 100 different HPV types that have been completely sequenced. 7 In addition, there appears to exist about 100 additional putative HPV types, with sequence information so far available only from PCR amplimers.…”
mentioning
confidence: 99%
“…Applying nested PCR with consensus primers revealed more positive results for EV HPV DNA in non-genital SK compared to healthy controls. [13] In nested PCR double genome amplification is used and the significant difference in positive results from two steps PCR genome amplification, strongly suggested a very low copy number for EV HPV DNA. [13] Gushi et al .…”
Section: Discussionmentioning
confidence: 99%
“…[13] In nested PCR double genome amplification is used and the significant difference in positive results from two steps PCR genome amplification, strongly suggested a very low copy number for EV HPV DNA. [13] Gushi et al . study detected mucosal HPV-18, 81, 6 in most of their samples.…”
Section: Discussionmentioning
confidence: 99%